Pyridinium Chlorochromate Supported on Alumina as an Efficient Oxidizing Agent for Oxidation of Alcohols Under Solvent Free Conditions - Niknam, Khodabakhsh (Asian Journal of Chemistry, 2016)
A rapid and convenient method is described for oxidizing alcohols into carbonyl compounds using pyridinium chlorochromate supported on alumina under solvent free conditions.